The Use of Kisspeptin Antibodies on Delayed Estrus in Rats - Risvanli, A.; Apaydin, A. M.; Bulut, H.; Timurkaan, N.; Saat, N. (Wiley-Blackwell Publishing, Inc, 2009)
[Abstract Not Available]
13th Annual Conference of the European-Society-of-Domestic-Animal-Reproduction -- SEP 09-12, 2009 -- Ghent, BELGIUM